A Rare Case of Fat Embolism Syndrome Following Multiple Long Bone Fractures - Talib, SH; Bhattu, S; Naik, M; Amjad, SA; Ibji, Abdullah (Medical Science: Trends and Innovations Vol. 9, 2025)
Fat embolism is defined by the presence of lipid droplets in the blood circulation blocking the small vessels. The term fat embolism syndrome refers to the clinical scenario following an insult that releases fat droplets in the circulation with resultant pulmonary and systemic involvement. A case of cerebral fat embolism – which developed 3 days after a roadside accident, in a young boy who suffered limb fracture of femur and tibia, was described. In cerebral fat embolism that manifests chiefly as disturbances of cerebral circulation and ischaemia, chest dyspnoea and pulmonary manifestations are strikingly lacking, leading to misdiagnosis or delay in its diagnosis. The present case chiefly developed cerebral fat embolism syndrome. Early recognition and comprehensive management is warranted for a better outcome. Aetiopathogenesis, presentation, diagnosis and treatment of cerebral fat embolism is briefly described and discussed. It was concluded that in isolated cerebral fat embolism, chest distress, dyspnoea and pulmonary manifestations are strikingly lacking leading to misdiagnosis or delay in its diagnosis.